Role of magnetic resonance imaging in spinal trauma - Ahuja, Ajit; Wadnere, Nitin; Behl, Simran (International Journal of Research in Medical Sciences, 2021)
Background: Magnetic resonance imaging (MRI) is the modality of choice for evaluation of ligamentous and other spinal cord, soft tissue structures, disc, and occult osseous injuries. Objective evaluate the role of MRI as a non-invasive diagnostic tool in patient with spinal trauma. Methods: This study was conducted in department of radiodiagnosis, Sri Aurobindo institute of medical sciences and PG institute, Indore and approval from the ethical and research committee. The duration of this study was April 2018 to May 2020. We included 60 patients of spinal trauma referred for MRI in this study. Results: In 32 (53.3%) patients the mode of injury was road traffic accidents, in 23 (38.3%) patients it was fall and in 5 (8.3%) patients the mode of injury was any other mode. There was significant difference seen between the MR cord hemorrhage, cord compression, and code transaction. Conclusions: MRI is an excellent modality for imaging of acute spinal trauma. Normal cord on baseline MRI predicts excellent outcome. When comparing patients with complete, incomplete spinal cord injury (SCI) and spine trauma without SCI, significant difference was seen in cord hemorrhage, cord transection, cord compression.